2020
DOI: 10.5771/0340-1758-2020-2-349
|View full text |Cite
|
Sign up to set email alerts
|

Amtsinhaber-Effekte in „unsicheren“ Wahlkreisen – eine Analyse anhand der Landtagswahlen in Brandenburg, Sachsen und Thüringen (1990 bis 2019)

Abstract: The elections in three East German Länder in 2019 did not only result in significant changes in the proportional vote share but also in severe shifts in constituency results between directly elected deputies . Against this backdrop this article analyses the election results in Brandenburg, Saxony, and Thuringia since 1990 . It shows that most of the constituencies have become contested . Hence, concepts dealing with “safe” constituencies for one party can, particularly in an increasingly fragmented party syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Besides attracting pragmatic donations, governing state branches are likely more salient in the public and media, encouraging citizens and partisans to donate money to a branch in state government. It has been shown that rerunning candidates have a higher propensity to be reelected in elections, as officeholders usually enjoy higher media coverage and public attention than their challengers (Egner and Stoiber 2008;Stoiber and Egner 2008;Träger, Pollex, and Jacob 2020).…”
Section: Party Financing In Federal Environmentsmentioning
confidence: 99%
“…Besides attracting pragmatic donations, governing state branches are likely more salient in the public and media, encouraging citizens and partisans to donate money to a branch in state government. It has been shown that rerunning candidates have a higher propensity to be reelected in elections, as officeholders usually enjoy higher media coverage and public attention than their challengers (Egner and Stoiber 2008;Stoiber and Egner 2008;Träger, Pollex, and Jacob 2020).…”
Section: Party Financing In Federal Environmentsmentioning
confidence: 99%
“…Empirical analyses on federal elections and, more recently, in eastern German states suggest that this effect holds for party politics at the German federal and state levels (Reiser, 2013). Specifically, incumbent members of Länder parliaments ( Landesparlamente ) and the federal parliament tend to have a better chance of re-election than candidates running for the first time (Träger et al, 2020).…”
Section: Party Functions Competition and Campaign Expenditurementioning
confidence: 99%